REAKSI PASAR TERHADAP MARKET SHOCK: KEBANGKRUTAN LEHMAN BROTHERS - Warsito Kawedar; Rr. Sri Handayani Handayani (Jurnal Ekonomi dan Bisnis, 2011)
The study aim to examine investor reaction to the market shock which coused by announcement of bankruptcy by America’s invesment company Lehman Brothers and to examine how is the difference reaction to market shock in the developed and emerging market.This study use t-test to examine market reaction that happened caused by Lehman Brothers bankruptcy. With totally sampel 44 main indeks around the world which listing in WSJ and 18 indeks for the country which belong to developed market, 20 indeks for the country which belong to emerging market. The result of this research show that the market overall react negatively to market shock which is Lehman Brothers bankruptcy and emerging market proof more react to market shock than developed market. This proof that Lehman Brothers bankruptcy contain information, the brittle of world financial system.Keyword : market shock, developed market, emerging market, return, stock price index